A nuclear protein NsiA from Epichloë festucae interacts with a MAP kinase MpkB and regulates the expression of genes required for symbiotic infection and hyphal cell fusion. Issue 4 (28th July 2020) - Tanaka, Aiko; Kamiya, Shota; Ozaki, Yoshino; Kameoka, Shinichi; Kayano, Yuka; Saikia, Sanjay; Akano, Fumitake; Uemura, Aiko; Takagi, Hiroki; Terauchi, Ryohei; Maruyama, Jun‐ichi; Hammadeh, Hamzeh Haj; et al.
Abstract: The endophytic fungus Epichloë festucae systemically colonizes the intercellular spaces of cool‐season grasses to establish a mutualistic symbiosis. Hyphal growth of the endophyte within the host plant is tightly regulated and synchronized with the growth of the host plant. A genetic screen to identify symbiotic genes identified mutant FR405 that had an antagonistic interaction with the host plant. Perennial ryegrass infected with the FR405 mutant were stunted and underwent premature senescence and death. The disrupted gene in FR405 encodes a nuclear‐localized protein, designated as NsiA for nuclear protein for symbiotic infection. Like previously isolated symbiotic mutants the nsiA mutant is defective in hyphal cell fusion. NsiA interacts with Ste12, a C2H2 zinc‐finger transcription factor, and a MAP kinase MpkB. Both are known as essential components for cell fusion in other fungal species. In E. festucae, MpkB, but not Ste12, is essential for cell fusion. Expression of several genes required for cell fusion and symbiosis, including proA/adv‐1, pro41/ham‐6, ham7, ham8, and ham9 were downregulated in the nsiA mutant. However, the NsiA ortholog in Neurospora crassa was not essential for hyphal cell fusion. These results demonstrate that the roles of NsiA and Ste12 orthologs in hyphal cell fusion are distinctive between fungal species. Abstract : Epichloë festucae systemically colonizes the intercellular spaces of cool‐season grasses to establish a mutualistic symbiosis. A gene encoding a nuclear protein, NsiA, was isolated as an essential gene for symbiotic infection and hyphal cell fusion. Expression of genes required for cell fusion were down‐regulated in the nsiA mutant. However, the NsiA ortholog in Neurospora crassa was not essential for hyphal cell fusion indicating that the roles of NsiAorthologs are distinctive between fungal species.